ANALISIS KINERJA SALES PROMOTION GIRL (SPG) PT ARINA MULTIKARYA DI KOTA TIMIKA - Imam Kurniawan; Muh. Sabir (CV. Adiba Aisha Amira, 2026)
This study aims to determine the performance of PT. Arina Multikarya's Sales Promotion Girls in Timika City and to determine the differences in the performance of PT. Arina Multikarya's Sales Promotion Girls in each store that sells Nestle products. The data collected in this study is qualitative data sourced from supervisors and assistants at stores that sell Nestle products, who were used as respondents using a questionnaire technique. The data was analysed using frequency distribution analysis and Friedman analysis. The results of the analysis show that the performance of PT. Arina Multikarya's Sales Promotion Girls in Timika City is in the ‘Good’ category, and there are differences in the performance of PT. Arina Multikarya's Sales Promotion Girls in each store that sells Nestle products.